2019
DOI: 10.1016/j.tmaid.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice (KAP) survey regarding antibiotic use among pilgrims attending the 2015 Hajj mass gathering

Abstract: Multifaceted and multidisciplinary approaches, both in KSA and in pilgrims' countries of origin, are needed to address antibiotic misuse during Hajj.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 46 publications
5
21
1
Order By: Relevance
“…Education level of the respondents affected the knowledge and attitude related to antibiotics and AMR. Previous studies from Nepal 27 , India 59 , Bhutan 47 , Saudi Arabia 60 , Hong Kong 61 , Malaysia 62 , South Korea 63 , Oman 64 , Greece 65 , and Lithuania 66 have echoed with our findings on the role of education. With higher education, respondents perhaps had good knowledge about proper use of antibiotics and adversities such as antibiotic resistance.…”
Section: Discussionsupporting
confidence: 88%
“…Education level of the respondents affected the knowledge and attitude related to antibiotics and AMR. Previous studies from Nepal 27 , India 59 , Bhutan 47 , Saudi Arabia 60 , Hong Kong 61 , Malaysia 62 , South Korea 63 , Oman 64 , Greece 65 , and Lithuania 66 have echoed with our findings on the role of education. With higher education, respondents perhaps had good knowledge about proper use of antibiotics and adversities such as antibiotic resistance.…”
Section: Discussionsupporting
confidence: 88%
“…Finally, although the analysis took into account reported use of antibiotics, it is possible that unreported use of antibiotics, which was likely widespread, might have confounded the difference between the groups. The frequent use of antibiotics reported in our study is consistent with other research which found that over 60% of pilgrims who travelled to Saudi Arabia carried antibiotics from their homeland with them and that 39.2% acquired non‐prescribed antibiotics in Saudi Arabia [26]. Other studies have reported misuse and overuse of antibiotics among pilgrims [27] which, if continued, will make Hajj pilgrimage at risk of spreading antibiotic resistance [28].…”
Section: Discussionsupporting
confidence: 89%
“…Similar observations were previously reported among Hajj pilgrims [7,14]. The inadequate handling, storage and disposal of medication pose a serious health and safety risk.…”
Section: Introductionsupporting
confidence: 88%
“…It is expected that these pilgrims will bring such medications with them on the pilgrimage [ 6 ]. In addition to drugs for chronic conditions, pilgrims also bring other types of medications with them for the pilgrimage in case they are needed, including analgesics, antipyretics and antibiotics [ 6 , 7 ]. Within the Kingdom of Saudi Arabia (KSA), pilgrims also access medications through physicians and pharmacists and from other pilgrims.…”
Section: Introductionmentioning
confidence: 99%